Preferences and beliefs in the marriage market for young brides - Abi Adams; Alison Andrew (Institute for Fiscal Studies (IFS), 2019)
Rajasthani women typically leave school early and marry young. We develop a novel discrete choice methodology using hypothetical vignettes to elicit average parental preferences over a daughter's education and age of marriage, and subjective beliefs about the evolution of her marriage market prospects. We find parents have a strong preference for delaying a daughter's marriage until eighteen but no further. Conditional on a marriage match, parents place little intrinsic value on a daughter's education. However, they believe the probability of receiving a good marriage offer increases strongly with a daughter's education but deteriorates quickly with her age on leaving school.
Keywords: J12; J16; I26; 330